An Integrated Knowledge Translation Experience: Use of the Network of Pediatric Audiologists of Canada to Facilitate the Development of the University of Western Ontario Pediatric Audiological Monitoring Protocol (UWO PedAMP v1.0) - Moodie, Sheila T. (SAGE Publications, 2011)
Pediatric audiologists lack evidence-based, age-appropriate outcome evaluation tools with well-developed normative data that could be used to evaluate the auditory development and performance of children aged birth to 6 years with permanent childhood hearing impairment. Bagatto and colleagues recommend a battery of outcome tools that may be used with this population. This article provides results of an evaluation of the individual components of the University of Western Ontario Pediatric Audiological Monitoring Protocol (UWO PedAMP) version 1.0 by the audiologists associated with the Network of Pediatric Audiologists of Canada. It also provides information regarding barriers and facilitators to implementing outcome measures in clinical practice. Results indicate that when compared to the Parents’ Evaluation of Aural/Oral Performance of Children (PEACH) Diary, audiologists found the PEACH Rating Scale to be a more clinically feasible evaluation tool to implement in practice from a time, task, and consistency of use perspective. Results also indicate that the LittlEARS(®) Auditory Questionnaire could be used to evaluate the auditory development and performance of children aged birth to 6 years with permanent childhood hearing impairment (PCHI). The most cited barrier to implementation is time. The result of this social collaboration was the creation of a knowledge product, the UWO PedAMP v1.0, which has the potential to be useful to audiologists and the children and families they serve.